Exploring Achievement of Motivation in the Nepalese Banks Post-Merger View - Khadka, Ajaya Kumar; Khadka, Srijana (Nepal Journal of Multidisciplinary Research, 2024)
Background: Employee motivation and achievement factors play an essential role in corporate decisions. This study examines the motivational factors that drive employees' motivation after a merger or acquisition. Its main objective is to explore the determinants of employees' motivation. Methods: The study employs a descriptive and causal-comparative research design. The study used a non-probability convenience sampling design of 235 employees from commercial institutions in Nepal. Results: Study findings reveal that employee achievement motivation is significantly positively correlated with personal factors, job characteristics, relationships with managers, and remuneration, as evidenced by correlation analysis. Conclusion: The impact of these factors on achievement motivation is determined by regression analysis, with job characteristics showing a primary significant influence. Novelty: The study suggests that human resource managers and decision-makers should consider the importance of incorporating a variety of factors to foster motivation in commercial institutions after the merger and to develop strategies for better employee engagement and performance.